Is the Student-Centered Learning Style More Effective Than the Teacher-Student Double-Centered Learning Style in Improving Reading Performance? - Dong, Yang; Wu, Sammy Xiaoying; Wang, Weisha; Peng, Shuna (Frontiers in Psychology, 2019)
Appropriate learning styles enhance the academic performance of students. This research compares and contrasts the popular effect of teacher-student double centered learning style (TSDCLS) and student-centered learning style (SCLS) on one’s reading, including reading comprehension, inference, main idea abstraction, and reading anxiety. One hundred and fifty one students in grade 4 from three groups (two experimental groups and one control group) participated in the experiment with 18 weeks’ reading comprehension training. The results showed that, first, both learning styles contributed to students’ reading comprehension, inference, main idea abstraction, and reading anxiety. Second, the TSDCLS contributed more to reading anxiety, and the SCLS contributed more to reading comprehension. Both learning styles had similar effects on inference and main idea abstraction. From the correlation test, excluding the correlation between SCLS and reading anxiety which was not significant, all other effects were significant. These findings are discussed along with implications and ideas for future research.